1994
DOI: 10.1021/bp00030a008
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Infection Conditions for Recombinant Protein Production in Insect Cell (Bm5) Suspension Culture

Abstract: The baculovirus/insect cell expression system is an efficient and practical method for the production of many active therapeutic proteins on a large scale. The advantages of suspension cultures have been demonstrated with the study of a baculovirus/insect cell (BmNPV/Bm5) expression system for the production of recombinant chloramphenicol acetyltransferase (CAT), a model heterologous protein. Key infection parameters such as infection time and multiplicity of infection were examined systematically for the maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 27 publications
1
9
0
1
Order By: Relevance
“…In the large-scale production of recombinant proteins, cultures infected at high-cell densities produce higher volumetric protein levels than those infected at low cell densities (Wong et al, 1996;Yang et al, 1996). However, high-cell density infections are limited by the nutrient supply from the medium (Radford et al, 1992;Radford et al, 1997b;Zhang et al, 1994). Recently, Tsao et al (1996) studied the production of a parvovirus B19 vaccine in insect cells coinfected with two baculoviruses.…”
Section: Discussionmentioning
confidence: 99%
“…In the large-scale production of recombinant proteins, cultures infected at high-cell densities produce higher volumetric protein levels than those infected at low cell densities (Wong et al, 1996;Yang et al, 1996). However, high-cell density infections are limited by the nutrient supply from the medium (Radford et al, 1992;Radford et al, 1997b;Zhang et al, 1994). Recently, Tsao et al (1996) studied the production of a parvovirus B19 vaccine in insect cells coinfected with two baculoviruses.…”
Section: Discussionmentioning
confidence: 99%
“…The abrupt decline in product yield has been partly reversed by nutrient supplementation and medium renewal (10,18,19). Nevertheless, in other reports no direct effects of cell density levels or of nutrient replacement strategies on productivity have been observed (20,21). It was suggested that this may indicate the presence of other simultaneous influences that should be examined for their role on infectivity and production at key points in the development of the population (22).…”
Section: Introductionmentioning
confidence: 96%
“…Likewise, an issue often overlooked is how well a particular insect cell line functions under different cell culture conditions. Generally, suspension culture provides the best environment for the optimal growth of insect cells and the production of virus and/or recombinant protein (Kioukia et al, 1995; Zhang et al, 1994; Deutschmann and Jaeger, 1994). The selection of an appropriate growth medium can be equally as important for the success of many production schemes (Akhnoukh et al, 1996; Hennsler and Agathos, 1994).…”
Section: Introductionmentioning
confidence: 99%